ESW4 enhanced scheme for WWW computing in wireless communication environments. - Hadjiefthymiades, Stathes
Mobile computing is considered of major importance to the computing industry for the forthcoming years due to the progress in the wireless communications domain. In this paper, we present a proxy-based architecture, called ESW4, which manages to accelerate Web browsing in wireless CPNs. Proxy caches, maintained in base stations, are constantly relocated to accompany the roaming user. We discuss a cache management scheme involving the relocation of full caches to the most candidate cells but also percentages of the cache to less likely neighbors. Relocation is performed according to the output of a movement prediction algorithm based on a learning automaton. The simulation of ESW4 shows substantial benefits for the end user.